1995
DOI: 10.1152/jn.1995.73.1.373
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy of the mental representation of upper extremity movements in healthy subjects

Abstract: 1. Differences in the distribution of relative regional cerebral blood flow during motor imagery and execution of a joy-stick movement were investigated in six healthy volunteers with the use of positron emission tomography (PET). Both tasks were compared with a common baseline condition, motor preparation, and with each other. Data were analyzed for individual subjects and for the group, and areas of significant flow differences were related to anatomy by magnetic resonance imaging (MRI). 2. Imagining movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

78
447
4
16

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 832 publications
(545 citation statements)
references
References 42 publications
78
447
4
16
Order By: Relevance
“…These critical issues have been raised in recent PET experiments in normal subjects. Conditions where subjects were intending actions and preparing for execution, mentally simulating actions, or observing actions performed by other people were compared (Decety et al, 1994(Decety et al, , 1997Grafton et al, 1996;Rizzolatti et al, 1996a;Stephan et al, 1995). The outcome of these studies is two-fold: First, there exists a cortical network common to all conditions, to which the inferior parietal lobule (area 40), the ventral premotor area (ventral area 6), and part of SMA contribute; second, motor representations for each individual condition are clearly specified by the activation of cortical zones which do not overlap between conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These critical issues have been raised in recent PET experiments in normal subjects. Conditions where subjects were intending actions and preparing for execution, mentally simulating actions, or observing actions performed by other people were compared (Decety et al, 1994(Decety et al, , 1997Grafton et al, 1996;Rizzolatti et al, 1996a;Stephan et al, 1995). The outcome of these studies is two-fold: First, there exists a cortical network common to all conditions, to which the inferior parietal lobule (area 40), the ventral premotor area (ventral area 6), and part of SMA contribute; second, motor representations for each individual condition are clearly specified by the activation of cortical zones which do not overlap between conditions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, involved in visually guided motor selection and control [6,16,45,62,68], the preSMA is Table 2 Experiment 2: anatomical specification, mean Talairach coordinates and known to project restrictively to the ventral subregions of reaching activation in this area [3,30,66] activated in the absence of the conscious intention, or even CAU, caudate nucleus; other abbreviations as in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have identified a ventral premotor area more ventrally than the above described area lying in the opercular cortex [49]. Table 1 Finally, it is possible that a part of vPMC extends into area Interestingly, the cerebellar activation for both visual conditions were located in the right superior cerebellum (main effect analysis for modality) revealed stronger signal (x516, y5248, z5224) while the cerebellar activations increases bilaterally in the vPMC ( Fig.…”
Section: Introductionmentioning
confidence: 86%
“…A more ventral and rostral part of the between an imagined trigger stimulus and the motor vPMC is also suggested to be involved in the imagination commands. This interpretation is related to findings linking of complex movements [49], preparation of imitated the caudal part of the dPMC to the learning of visual movements [24], or imitation of movements in general conditional tasks both in monkeys and humans [17,33]. [41, 44,45].…”
Section: Introductionmentioning
confidence: 92%